Sonographic weight estimation in fetal macrosomia: influence of the time interval between estimation and delivery - Faschingbauer, Florian; Dammer, U.; Raabe, E.; Schneider, M.; Faschingbauer, Cornelia; Schmid, M.; Mayr, Andreas; Schild, R. L.; Beckmann, Matthias; Kehl, Sven (Archives of Gynecology and Obstetrics, 2015)
To evaluate the influence of the time interval between examination and delivery on the accuracy of sonographic weight estimation (WE) in fetal macrosomia.896 singleton pregnancies (birth weight > 4,000 g) with a total of 1,281 sonographic weight estimations were included in this retrospective cohort study. Fetuses were divided into six groups with regard to the time interval between estimation and delivery: group 1: scan-to-delivery interval: 0 days; group 2: scan-to-delivery interval: 1-3 days; group 3: scan-to-delivery interval: 4-7 days; group 4: scan-to-delivery interval: 8-14 days; group 5: scan-to-delivery interval: 15-21 days; group 6: scan-to-delivery interval: 22-42 days. The accuracy of WE was compared between five commonly used formulas using means of percentage errors (MPE), random error, medians of absolute percentage errors (MAPE), and proportions of estimates within 10 % of actual birth weight.Significant differences were found between the time interval groups with regard to MAPE and MPE values (p < 0.001). All formulas showed a systematic underestimation of fetal weight (negative MPEs) (p < 0.05). MPE values were closest to zero in time interval group 1 and 2. From group 3 to 6, a continuous decrease was observed. The lowest MAPE was found with the Merz formula in group 1 and 2. Values increased continuously from group 3 to 6. Differences between time interval group one and three did not reach statistical significance.WE in fetal macrosomia shows the best results when examinations are performed within 7 days before delivery, using the formula of Merz et al. Accuracy significantly decreases after this time period.
EVALuna2:5469